Using reflective journals as an assessment tool to support mental well-being - Kamarulzaman, Wirawani; Ibrahim, Hasniza; Abd Karim, Aishah Hanim (Asian Scholar Network, 2024)
Growing concerns about university students' mental health have highlighted the need for strategies that provide both academic and emotional support. Reflective journaling has emerged as a promising assessment tool that offers students a structured means to express emotions, develop self-awareness, and support mental well-being. However, research on students' perceptions of reflective journaling and its impact on mental health remains limited. This qualitative study examines students' experiences with reflective journaling as part of their academic journey and its perceived benefits for mental health. Semi-structured interviews with six undergraduate students from a public university revealed several key themes, including the role of reflective journaling in fostering positive thinking and self-awareness, offering a safe outlet for emotional expression, managing anxiety and overthinking, enhancing a sense of control and perspective, and supporting problem-solving skills. These findings suggest that reflective journaling can act as both an assessment tool and a mental health resource, fostering resilience and promoting holistic student development. Future research could explore the application of reflective journaling across disciplines and develop tailored prompts to address specific cognitive and emotional challenges encountered by students. Educational institutions may consider integrating reflective journaling into mental health support frameworks, providing a holistic approach that aligns with students' academic and emotional needs